PENGARUH DPK, NPF, CAR, EKUIVALEN BAGI HASIL, DAN SERTIFIKAT IMA TERHADAP PEMBIAYAAN BANK UMUM SYARIAH TAHUN 2012-2014 - Riska Robiyanti Erlita (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2016)
This research is included as applied research. Based on the objective, it is classifid as quantitative specifically descriptive analytical. Population used in this research is Public Sharia Bank in Indonesia. Sampling is determined by using purposive sampling method, in which 33 samples are taken. Analysis is conducted by having double regression analysis by doing classical assumption test in the beginning. This study was conducted to examine the influence of DPK (Third Party Fund), NPF (Non Performing Financing), CAR (Capital Adequacy Ratio), profit sharing equivalenceratio and the IMA Certificates toward Financing ofPublicSharia Bank in 2012 to 2014 using quarterly data. The analysis showed that only two variables that significantly influence the financing, which are third-party funds (DPK), and NPF (Non Performing Financing) while CAR (Capital Adequacy Ratio), profit sharing equivalence and IMA certificates are not proven as significant.